2017
DOI: 10.1002/csr.1461
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Corporate Climate Change Disclosure for European Firms

Abstract: This study identifies the determinants of climate change disclosure under the prism of sustainable development in European context. The selected variables involve environmental performance, ownership structure, and verification of climate change initiatives. Cross‐sectional data derived from the Bloomberg terminal of the European 500 index concerning 215 firms in the year 2014 are employed. The novelty of the present study stands on the use of proxies for climate change disclosure by adopting the Climate Perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 65 publications
5
88
1
1
Order By: Relevance
“…Giannarakis, Zafeiriou, Arabatzis, and Partalidou (2018) argue that climate change disclosure is an effective tool to limit information asymmetry for shareholders and stakeholders. Giannarakis, Zafeiriou, Arabatzis, and Partalidou (2018) argue that climate change disclosure is an effective tool to limit information asymmetry for shareholders and stakeholders.…”
Section: The Relationship Between Environmental Engagement and Bankmentioning
confidence: 99%
See 1 more Smart Citation
“…Giannarakis, Zafeiriou, Arabatzis, and Partalidou (2018) argue that climate change disclosure is an effective tool to limit information asymmetry for shareholders and stakeholders. Giannarakis, Zafeiriou, Arabatzis, and Partalidou (2018) argue that climate change disclosure is an effective tool to limit information asymmetry for shareholders and stakeholders.…”
Section: The Relationship Between Environmental Engagement and Bankmentioning
confidence: 99%
“…The 1995 Kyoto Protocol and, more recently, the Paris Conference (2015) confirm the importance ascribed to this theme worldwide. Giannarakis, Zafeiriou, Arabatzis, and Partalidou (2018) argue that climate change disclosure is an effective tool to limit information asymmetry for shareholders and stakeholders. Prior literature recognizes environmental protection as a pillar of CSR (Renneboog et al, 2008).…”
Section: The Relationship Between Environmental Engagement and Bankmentioning
confidence: 99%
“…The investigation, its connection with the agency theory, and the approach adopted to evaluate the fallout of carbon emissions on financial performance of firms enrich the existing empirical and methodological evidence (Eisenhardt, 1989;Giannarakis, Zafeiriou, Arabatzis, & Partalidou, 2018;Holmstrom & Milgrom, 1991;Hopwood, 1972).…”
mentioning
confidence: 99%
“…Hackston & Milne, 1996;Cormier & Gordon, 2001;Brammer & Pavelin, 2008;Liu & Anbumozhi, 2009;Sun et al, 2010;Clarkson et al, 2011;Zeng et al, 2012;Sulaiman et al, 2014;Juhmani, 2014;Akrout & Othman, 2016;Yildiz et al, 2016;Welbeck et al, 2017;Vogt et al, 2017;Deswanto & Siregar, 2018;Kolsi & Attayah, 2018;Kılıç & Kuzey, 2019). However, some studies found that increases in profitability contribute to more transparency in environmental issues (Pahuja, 2009;Setyorini & Ishak, 2012;Singhania & Gandhi, 2015;Braam et al, 2016;Ahmadi & Bouri, 2017;Giannarakis et al, 2017;Ismail et al, 2018;Elshabasy, 2018;Kouloukoui et al, 2019;Wang & Zhang, 2019). The reason for the positive relation between profitability and environmental disclosure is that more profitable firms have more ability to fund the costs of environmental reporting (Freedman & Jaggi, 2005: 221;Brammer & Pavelin, 2006: 1174Andrikopoulos & Kriklani, 2013: 59).…”
Section: Profitabilitymentioning
confidence: 99%